Analiza przedsiębiorstw z Dolnego Śląska jako nabywców usług ubezpieczeniowych : podejście klasyfikacyjne - Borda, Marta; Kwiecień, Ilona (Analysis of the Lower Silesian Enterprises as the Insurance Services Buyers : Classification Approach, 2007)
The paper presents the analysis of business entities as the insurance services buyers based on questionnaire surveys conducted by the authors on the sample of the Lower Silesian firms. Firstly, the obtained results have been compared with similar surveys conducted countrywide by Polish Central Statistical Office. Next, the selected taxonomic methods have been applied in order to classify the respondents according to the range of using insurance services in their activity. The presented analysis has important practical significance for the insurance companies, interested in modification of their offer in terms of the enterprises' expectations, as well as for the insurance intermediaries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 402-410